Study of Examination and Achievement as Dimension of Psychological Stress among Science Students - Narendra Kumar; Rajive Kumar (JOURNAL OF INDIAN EDUCATION, 2016)
This study attempts to assess the examination and achievement as dimension of psychological stress among senior secondary science students studying in different types of institutions. A sample of 631 students was randomly selected from the schools recognised by different boards in Meerut district. They were administered Psychological Stress Scale for Science Students (PSSSS) developed by the researcher himself. Mean, S.D., F-test and t-test were used to analyse the data. Results show that male and female science students do not differ significantly on psychological stress dimension examination and achievement. While significant difference was observed between rural and urban science students, rural science students were found to be more stressed than urban science students. Further, significant difference was observed among the students of different types of institutions. Highest psychological stress due to its dimension examination and achievement was found in the students of U.P. Govt. Aided Schools (GAS) and lowest in the students of Kendriya Vidyalayas (KVs). Similarly, significant difference was observed between the students of different types of boards UPB and CBSE, UPB and ISC. No significant difference was observed between the students of CBSE and ISC. Highest psychological stress due to examination and achievement was found in the students of UPB and lowest in the students of ISC.